Thermoregulation (Iowa NOC) In: Nursing outcomes classification (NOC): Iowa outcomes project. - Johnson M; Maas M (Thermoregulation (Iowa NOC) In: Nursing Outcomes Classification (NOC): Iowa Outcomes Project, 1997)
SCOPE NOTE: Balance among heat production, heat gain, and heat loss. Use only as a specific Iowa Nursing Outcomes Classification. Copyright (c) 1997, Mosby-Year Book, Inc. CINAHL EDITORIAL SEARCH SUGGESTION: The term THERMOREGULATION (IOWA NOC) is used for indexing when articles specifically concern the term or research about the term. For citations that concern the general topic or topics related to the term, consider searching the subject heading: BODY TEMPERATURE REGULATION.